## [討論]加減乘除等於M (Jacky asked)

### [討論]加減乘除等於M (Jacky asked)

eg1.M(1,1,3,8)=28

8/(3+1)-1=1
8/(3+1)*1=2
8/(3+1)+1=3
(8-3-1)*1=4
(8-3)*1*1=5
(8-3+1)*1=6
8-3+1+1=7
8*(3-1-1)=8
8+3-1-1=9
(8+3-1)*1=10
(8+3)*1*1=11
(8+3+1)*1=12
8+3+1+1=13
(1+1)*3+8=14
(3-1)*8-1=15
(3-1)*8*1=16
(3-1)*8+1=17
(3-1)*(8+1)=18
(1+1)*8+3=19
(8-1)*3-1=20
(8-1)*3*1=21
(3+8)*(1+1)=22
3*8*1-1=23
3*8*1*1=24
3*8*1+1=25
3*8+1+1=26
(8+1)*3*1=27
(8+1)*3+1=28

eg2.M（1、2、4、7）=37

(4-1)x(7-2)=15
4x(7-2-1)=16
2x7+4-1=17
2x7+4x1=18
2x7+4+1=19
(7-2)x4x1=20
(4-2+1)x7=21
(7+4)x2x1=22
(7+4)x2+1=23
4x(7-2+1)=24
4x7-2-1=25
4x7-2x1=26
(4-1)x(2+7)=27
4x7x(2-1)=28
4x7+2-1=29
4x7+2x1=30
4x7+2+1=31
4x(7+2-1)=32
(7+4)x(2+1)=33
(1+7)x4+2=34
7x(2+4-1)=35
1x4x(2+7)=36
(2+7)x4+1=37

jimboqoo

M(1,2,4,9)=40

9-4*2*1=1
9+1-4*2=2
9/(4-2+1)=3
(9-1)/(4-2)=4
(9+1)/(4-2)=5
9-1-4/2=6
9*1-4/2=7
(9-4-1)*2=8
(9+1)/2+4=9
(9-4)*2*1=10
9+4/2*1=11
9/(2+1)*4=12
9+4*(2-1)=13
9*2-4*1=14
(9-4)*(2+1)=15
(9-1)*4/2=16
9*(4-2)*1=18
9*(4-2)+1=19
(9+1)*4/2=20
(9-2)*(4-1)=21
9*2+4*1=22
9*(2+1)-4=23
(9+1)*2+4=24
9*(4-1)-2=25
(9+4)*2*1=26
9*(4/2+1)=27
(9-2)*1*4=28
(9-2)*4+1=29
(9-1)*4-2=30
9*(2+1)+4=31
(9+1-2)*4=32
9*4-2-1=33
9*4-2*1=34
9*4-2+1=35
9*4+2-1=37
9*4+2*1=38
9*4+2+1=39
(9+2-1)*4=40

bell